(untitled) (Ticontre. Theory Text Translation, 2020)
This article analyzes the dialogue In famiglia, which is centered on Helen, real woman-myth, object of desire, exaltation, contempt, defense and accusation. Helen is a figure of titanic irrational and represents a fully artemidean and aphroditic femininity, fully bearing the risk that such a connection entails. Helen is bound with fault, death, and humanity’s fate of suffering, and her figure is vastly spread in classical literature. Pavese takes from this tradition, exploring the archaic substrate of Helen’s myth, and draws, sometimes explicitly, from Euripides’ tragedies, reinterpreting this complex character through an allusive game, which problematizes with subtle irony the tragic conflict at the very base of human existence.